Comparative Characterization of Biomechanical Behavior and Healing Profile of a Novel Ultra-High-Molecular-Weight Amorphous Poly-L-Lactic Acid Sirolimus-Eluting Bioresorbable Coronary Scaffold. (October 2016) - Cheng, Yanping; Gasior, Pawel; Shibuya, Masahiko; Ramzipoor, Kamal; Lee, Chang; Estrada, Edward A.; Dokko, Daniell; McGregor, Jenn C.; Conditt, Gerard B.; Kaluza, Greg L.; Granada, Juan F.
Abstract : Background—: Clinically available bioresorbable scaffolds (BRS) rely on polymer crystallinity to achieve mechanical strength resulting in limited overexpansion capabilities and structural integrity when exposed to high-loading conditions. We aimed to evaluate the biomechanical behavior and vascular healing profile of a novel, sirolimus-eluting, high-molecular-weight, amorphous poly-L-lactic acid–based BRS (Amaranth BRS). Methods and Results—: In vitro biomechanical testing was performed under static and cyclic conditions. A total of 99 devices (65 Amaranth BRS versus 34 Absorb bioresorbable vascular scaffold [BVS]) were implanted in 99 coronary arteries of 37 swine for pharmacokinetics and healing evaluation at various time points. In the Absorb BVS, the number of fractures per scaffold seen on light microscopy was 6.0 (5.0–10.5) when overexpanded 1.0 mm above nominal values (≈34%). No fractures were observed in the Amaranth BRS group at 1.3 mm above nominal values (≈48% overexpansion). The number of fractures was higher in the Absorb BVS on accelerated cycle testing over time (at 24K cycles=5.0 [5.0–9.0] Absorb BVS versus 0.0 [0.0–0.5] Amaranth BRS). Approximately 90% of sirolimus was found to be eluted by 90 days. Optical coherence tomography analysis demonstrated lower percentages of late scaffold recoil in the Amaranth BRS at 3 months (Amaranth BRS=−10±16.1% versus Absorb BVS=10.7±13.2%; P =0.004). Histopathology analysis revealed comparable levels of vascular healing and inflammatory responses between both BRSs up to 6 months. Conclusions—: New-generation high-molecular-weight amorphous poly-L-lactic acid scaffolds have the potential to improve the clinical performance of BRS and provide the ideal platform for the future miniaturization of the technology.